Microbiological evaluation of sunned meat selled at free fairs in the city of Itapetinga-BA - Domingues, Robson de Queiros; Barbosa, Monique Costa; Araújo, Antônia Cardoso Mendes de; Lins, Raphael Patury; Ponciano, Carolina da Silva; Silva, Jaqueline de Jesus; Oliveira, Geisa Sales; Menezes, Lígia Miranda (Seven Editora, 2023)
Sun-dried meat is a product marketed throughout Brazil, especially in the Northeast region. It does not have its own legislation that supervises its quality standard, which makes it subject to numerous sources of contamination. The objective of this study was to evaluate  the hygienic-sanitary conditions of production  of sun-dried meat sold in six establishments, open markets, in the municipality of Itapetinga-BA. Microbiological analyses (halophilic mesophiles, Staphylococcus, Salmonella, total and thermotolerant coliforms) were performed at the Food Microbiology Laboratory of UESB. From the results obtained, sample C, in sample 1 considering halophilic mesophilic microorganisms, presented the lowest contamination rate, 7.47 x 102 CFU/g. Sample B presented the highest contamination rate for Staphylococcus aureus, 9.3 x 103 CFU/g. For total coliforms, sample B presented a contamination number of 1.1 x 103 NMP/g. The remaining samples remained within the standard allowed for total coliforms. In the second collection, all samples showed values above those allowed by law for mesophils and Staphylococcus aureus. For coliforms, there was a reduction in the number of contamination to the samples. The presence of Salmonella spp. was found. in all samples on the first day of collection, however, on the second day, only sample C was absent. Therefore, according to the establishments studied, none of them met the criteria established by the current legislation, presenting flaws regarding the safety of the food. It is suggested that establishments adopt the procedures of good manufacturing practices, with the use of preventive measures, in order to ensure the safety of food products. DOI:https://doi.org/10.56238/interdiinovationscrese-004